Effect of the function of polymorphonuclear leukocytes and interleukin-1 beta on wound healing in patients with diabetic foot infections - GÜRBÜZ, BURÇAK; SOYOĞUL GÜRER, ÜMRAN (W B SAUNDERS CO LTD, 2007)
Objectives: This study was carried out prospectively to determine the effect on prognosis of phagocytic activity index (PAI) and intracellular killing activity (IKA) of polymorphonuclear leukocytes (PMNL), and the levels of interleukin-1 beta (IL-1 beta) on prognosis in patients with diabetic foot infection (DFI). Methods: The evaluation of PAI and IKA in PMNL and the levels of IL-1 beta were performed at the beginning and in the second and fourth weeks of therapy in all diabetic patients, who were categorized into a heating group (HG) and a non-heating group (NHG) on the basis of therapy results. Results: Sixty-six cases (38 diabetic patients and 28 non-diabetic controls) were included in the study. Full recovery was observed in 23 HG patients, whereas 15 (NHG) patients were unresponsive to treatment and nine patients were subjected to amputation at the end. At the baseline, PAI, IKA and IL-1 beta levels in FIG were not significantly different compared to those of NHG, but at weeks 2 and 4, PAI and IKA levels were significantly higher and IL-1 beta levels were significantly lower than those in NHG. On the other hand, at the baseline, PAI and IKA values in HG were significantly lower and IL-1 beta levels were significantly higher in comparison with the controls. However, no significant difference was observed at week 2 or 4. Conclusion: Our results suggest that the PMNL functions and IL-1 beta regulation deteriorated in patients with DFI, and that such deteriorations might indicate inefficient therapeutic responses in patients with diabetes mellitus. (C) 2006 The British Infection Society. Published by Elsevier Ltd. ALL rights reserved.
Keywords: diabetic foot infections; polymorphonuclear leukocyte function; interleukin-1 beta; IN-VITRO; MACROPHAGES; CYTOKINE; ACID